Efficacy of telavancin alone and in Combination with ampicillin in a rat model of enterococcus faecalis endocarditis (2020)
We first assessed telavancin (TLV) pharmacokinetics in rats after a single subcutaneous dose of 35 mg/kg of body weight. The pharmacokinetic data were used to predict a TLV dose that simulates human exposure, and the efficacy of TLV was then evaluated using a TLV dose of 21 mg/kg every 12 h against Enterococcus faecalis OG1RF (TLV MIC of 0.06 g/ml) in a rat endocarditis model with an indwelling catheter. Therapy was given for 3 days with TLV, daptomycin (DAP), or ampicillin (AMP) monotherapy and with combinations of TLV plus AMP, AMP plus gentamicin (GEN), and AMP plus ceftriaxone (CRO); rats were sacrificed 24 h after the last dose. Antibiotics were given to simulate clinically relevant concentrations or as used in other studies. TLV treatment resulted in a significant decrease in bacterial burden (CFU per gram) in vegetations from 6.0 log10 at time 0 to 3.1 log10 after 3 days of therapy. Bacterial burdens in vegetations were also significantly lower in the TLVtreated rats than in the AMP (P 0.0009)- and AMP-plus-GEN (P 0.035)-treated rats but were not significantly different from that of the AMP-plus-CRO-treated rats. Bacterial burdens from vegetations in TLV monotherapy and TLV-plus-AMP-and-DAP groups were similar to each other (P 0.05). Our data suggest that further study of TLV as a therapeutic alternative for deep-seated infections caused by vancomycinsusceptible E. faecalis is warranted.